Attitudes and Behaviors of Female Nursing Students Toward Plagiarism - Halabi, Jehad; Suliman, Wafik (DIRASAT: EDUCATIONAL SCIENCES, 2019)
Student’s academic misconduct breaches the trustworthiness of their knowledge. Academic institutions usually emphasize that any breach of academic honesty would be regarded as a disciplinary matter. This descriptive study focuses on plagiarism as one form of academic misconduct. The purpose is to investigate the attitudes and behaviors of female nursing students toward plagiarism in relation to their level of education, and to study ethics, research, and clinical nursing courses. The study uses a convenience sample of 134 female students from one university (57 junior and 77 senior), and a reliable questionnaire that consists of 7 scenarios on plagiarism for data collection. Results show significant intergroup differences. Of major concern are conformance between honest attitudes and behaviors of junior students, in contrast to conformance in dishonest attitudes and behaviors of senior students, students who study research, and those who study clinical nursing toward: “copying verbatim (word-for-word) from the internet and other published sources and lists them as references”; and toward “helping a friend by writing an assignment for him/her”. In conclusion, the study suggests the enhancement of the academic integrity among students, and recommends further research on the ethical responsibility of faculty members and college management toward controlling academic misconduct.